Territorial implications between different categories of nature conservation units in Brazil and the political-pedagogical conceptions of environmental education - Ferla, Marcio Ricardo; Nabozny, Almir (GEOUSP Espaço e Tempo (Online), 2022)
The Nature Conservation Units (CUs) are territories established by the Brazilian State. They involve power relations related to the control of natural resources. The Environmental Education (EE) is placed as a strategic dialogue with the agents involved with the CU territorialization. The EE, from the perspective of a social field, presents three macro-trends of political-pedagogical conceptions: the critical one, the conservationist one and the pragmatic one. An amount of 254 federal UCs were investigated through online questionnaires, aiming at articulating the patterns of regulation of UCs territories with the territorialities of EE practices. It was verififed that despite the existence of an unique institutional guideline, the CUs related to the Integral Protection Group presented an inclination towards the critical conservationist political-pedagogical conception, whereas the CUs of the Sustainable Use tended towards the critical political-pedagogical conception. This means that different forms of UCs territorialization tend to certain political-pedagogical conception of EE, regardless the institutional guidelines.